Study of prevalence for lactose malabsorption in malnutrition - Painkra, Sameer Kumar; Mandavi, Dhannu Ram (International Journal of Research in Medical Sciences, 2018)
Background: Milk is the major food in the diet of the infant mammal and consequently has always attracted considerable interest from the physician, the industrialist and the mother. The concentration of lactose in milk varies from species to species. Main objective is to study the prevalence of malabsorption in malnutrition. Methods: Sixty-seven children ranged between ages of 6 months to 3 years, of both sex and varying grades of malnutrition, were studied. Study conducted between July 1979-December 1979. All children were grouped into 4 grades of malnutrition according to Indian Academy of Pediatrics recommendation. Results: Out of 67 cases, 50 were followed up. Severe malnutrition of grades III and IV (less than 60 percent of expected body weight) comprises 58.2 percent (39 out of 67) in first seen group, and 52 percent (26 out of 50) in follow up group. 59.7 percent Males and 40.3 percent females in first seen cases. 58 percent males and 42 percent females in follow up cases. 24 cases (53.33 percent) of lactose malabsorbers were males and 21 cases (46.67 percent) were females. Conclusions: Lactose malabsorption is common in protein-energy malnutrition. This can be determined by simple ward tests and abnormal lactose tolerance curve after oral lactose load. Lactose malabsorption increases with the severity of malnutrition. Malnutrition leads to lactose malabsorption and lactose malabsorption is an important contributory factor in production of malnutrition.